2021
DOI: 10.3897/folmed.63.e55838
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of amorphous solid dispersion techniques to enhance solubility of febuxostat

Abstract: Febuxostat is a selective inhibitor of xanthine oxidase and belongs to BCS class II drugs having low solubility and high permeability. Solubility is the most important parameter which directly affects dissolution, absorption and bioavailability of the drugs. There are different techniques by which we can improve solubility and dissolution rate of poorly soluble drug. Amorphous solid dispersion is one of the methods which can improve solubility as well as powder characteristics. The aim of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These results showed that the measured solubility statistics for FXT were in good agreement with the literature that has been published [ 9 , 32 ]. FXT solubility has also been improved using different techniques, such as solid dispersion, nanomatrix, and nanoemulsion approaches [ 61 , 62 , 63 ]. The comparative solubility data of FXT in PEG 400 with reported solubility approaches are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that the measured solubility statistics for FXT were in good agreement with the literature that has been published [ 9 , 32 ]. FXT solubility has also been improved using different techniques, such as solid dispersion, nanomatrix, and nanoemulsion approaches [ 61 , 62 , 63 ]. The comparative solubility data of FXT in PEG 400 with reported solubility approaches are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The comparative solubility data of FXT in PEG 400 with reported solubility approaches are summarized in Table 3 . The equilibrium solubility of FXT using nanomatrix and solid dispersion approaches has been reported as 92.91 and 632.0 µg mL −1 , respectively [ 61 , 62 ]. The equilibrium solubility of FXT in PEG 400 was 7053 µg mL −1 in this work, which was approximately 76- and 11-fold higher than its reported solubility in nanomatrix and solid dispersion, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent research trends of Febux were SD formulations ( Amin et al, 2020 , El Shenawy et al, 2019 , Kaur et al, 2020 , Moinuddin et al, 2020 , Patel et al, 2021 ), as well as self-micro and nano-emulsifying formulations ( Al-Amodi et al, 2020 , Habib et al, 2021 , Rangaraj et al, 2019 ), nanostructure lipid carriers ( Varia et al, 2022 ), and co-crystal ( Jagia et al, 2022 ). Among them, the SD manufacturing method was selected owing to the reason that our group has established a drug solubilization method with an SD manufacturing method, and has an approach and manufacturing technology accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Febux-SD formulations were prepared using different polymers (Kolliphor P® [188 and 237] and Eudragit RLPO). Then, SD manufacturing methods using hot melt (fusion), solvent evaporation, and spray drying techniques were compared ( Patel et al, 2021 ). Febux-co-processed excipient formulations were prepared with crospovidone and microcrystalline blend (1:1) with solvent evaporation method ( Kaur et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The XRD pattern of S-SNEDDS showed an absence of drug instability in its polymorphic transitions when the transformation of L-SNEDDS to S-SNEDDS was occurring. While low-intensity characteristic peaks of the drug were visible in XRD patterns of S-SNEDDS could be due to the added excipient interferences at specific angular responses and even the non-appearance of a few peaks indicates the transformation of FXT from crystalline to unstructured form in S-SNEDDS34 .SEM:The surface topology of the S-SNEDDS was checked using SEM, and images of the same are depicted in Fig.7Aand Fig.7B. SEM studies…”
mentioning
confidence: 99%